Certain Psychological Aspects In The Activities Of Scientific And Research Institutions Of Forensic Examination - Uhrovetskyi, Oleh; Kurdes, Oleg; Ivanović, Aleksandar (Archives of Criminology and Forensic Sciences, 2026)
This research paper studied certain psychological aspects in the activities of scientific and research institutions of forensic examination, including psychology of management, moral-psychological climate in the staff, timely elimination of destructive conflict situations, social-psychological support of innovative process while reforming these institutions, training system of psychological preparation of management staff. Scientific principles for improving of psychology of management and psychological training of management staff are outlined. The structural model of personal qualities which should be possessed by an applicant for a managerial position at scientific and research institution of forensic examination. The need to improve the state of staffing management positions with persons who are capable of managing people based on their moral, business and psychological qualities was confirmed. For this purpose, it is proposed to reform the existing personnel departments of scientific and research institutions of forensic examinations and to create on their basis personnel management units with personnel management functions, taking into account modern domestic and foreign experience.